Mapeamento do processo em laboratórios de análises clínicas para identificação de perdas produtivas - Souza, Mariane Cásseres de (Universidade do Vale do Rio dos Sinos, 2015)
Health is one of the most important economic activities in Brazil and worldwide. The health institutions in Brazil work to achieve a technical and managerial efficiency through identification, control and quality management. Some concerns about the quality of services dedicated to the health care reflect to the new requirements, where is included ordinances and resolutions that can give assistance during the execution of activities in the field of clinical analysis. This research aimed to analyze the main points of losses and as the implementation of management systems associated with the certification standards of the sector, can assist in improving clinical laboratories processes. It is classified as exploratory and qualitative research, having been adopted the multiple case-study, conducted at four clinical laboratories, located on the northern coast of Rio Grande do Sul State - Brazil. As a result, it shows that 77.16% of the laboratory process is characterized by activities that do not add value to the customer, being 28.46% movement losses and 48.70% losses due the waiting. Only 22.84% of activities were considered to aggregating value to the customer. Regarding the Management Systems, the certification standards ISO 9001, 17025 and 15189 can help reduce the losses with the implementation of technical and managerial requirements for management. In this sense, the research intended to expand knowledge related to the Quality Management Systems in clinical laboratories, coupled with certification standards in that field.
Keywords: Mapeamento do processo; Perdas produtivas na saúde; Laboratórios de análises clínicas; Normas de certificação; Lean na saúde; Mapping process; Production waste in health; Laboratories of clinical analysis; Certification standards; Lean in healthcare; ACCNPQ::Engenharias::Engenharia de Produção